2022
DOI: 10.21608/ejar.2022.129261.1220
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Anatomical Characteristics of Some Mango Tree Cultivars Infested by Two Mealybugs, Planococcus Citri (Risso) and Icerya Seychellarum (Westood) in Egypt

Abstract: Anatomical and biochemical parameters have been studied for six mango leave cultivars (Balade, Skare, Zebda, Fagri Klan, Alphonso and Ewais) infested with two mealy bugs, Planococcus citri (Risso) and Icerya seychellarum (Westood). Ammonium humate 3% was used as a bio insecticide to control these pests during the period from April 2020 till March 2021 under field condition. Statistical analysis showed that Ammonium Humate had positive effects on reducing the populations of both I. seychellarum and P. Citri. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The mealy bugs for cotton plants include, Phenacoccus solenopsis, Ferrisa virgata, Maconellicoccus hirsutus, etc., among which P. solenopsis is the dominant species for cotton plants in the Indian subcontinent [20]. It has been reported that the mango tree is also infected with the two types of mealy bugs, Planococcus citri and Icerya seychellarum [21]. Leaf-hoppers are also members of the Hemipteran group but belong to Cicadellidae which also causes massive crop damage in the Indian subcontinent [22].…”
Section: Major Insect Pests To the Crop Plantsmentioning
confidence: 99%
“…The mealy bugs for cotton plants include, Phenacoccus solenopsis, Ferrisa virgata, Maconellicoccus hirsutus, etc., among which P. solenopsis is the dominant species for cotton plants in the Indian subcontinent [20]. It has been reported that the mango tree is also infected with the two types of mealy bugs, Planococcus citri and Icerya seychellarum [21]. Leaf-hoppers are also members of the Hemipteran group but belong to Cicadellidae which also causes massive crop damage in the Indian subcontinent [22].…”
Section: Major Insect Pests To the Crop Plantsmentioning
confidence: 99%
“…Around 69 species, including (Mangifera indica L.), are farmed in Egypt, particularly in the Ismailia Governorate (Anacardiaceae). Unfortunately, a heavy infestation of mealybugs, such as the Planococcus citri (Risso), significantly damages mango trees in all areas and decreases mango productivity (Mokhtar, 2022). Although female mealybugs acquire cushiony scales on their dorsal side, which decreases their exposure to the uptake of insecticides, mealy bugs have a cryptic character, making their management difficult and difficult ineffectual (Arshad et al, 2015).…”
Section: Introductionmentioning
confidence: 99%